2005
DOI: 10.1111/j.1095-8649.2005.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress‐induced alterations of antioxidants in the freshwater fish Channa punctata Bloch

Abstract: The effect of elevated temperature on the antioxidants in the freshwater fish Channa punctata was investigated. Fish stressed with an elevated temperature of 12 C, range AE 1 C over the ambient temperature for 3 h showed a significant (P < 0Á05-0Á01) reduction in the levels of antioxidants: reduced glutathione (GSH) and non-protein thiols. Activity of glutathione reductase was also reduced in all the tissues (liver, kidney and gills) after 3 h of heat stress and 24 h recovery. Catalase (CAT) showed enhanced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 44 publications
2
20
1
Order By: Relevance
“…Furthermore, published work in eelpout and juvenile rainbow trout has shown seasonal reductions in GST activity during the fall-winter seasonal transition (Ronisz et al 1999). The transient increases in GST activity observed in the current study at week 3 may be attributed to increased production of reactive oxygen species at higher temperatures (increasing metabolic rate) eliciting antioxidant responses that may interfere with concurrent thermomodulatory adaptations (Kaur et al 2005). Ration-restricted and fasted fish also exhibit peak GST activities at week 3, but to a lesser extent than seen in control fish.…”
Section: Gst Activitymentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, published work in eelpout and juvenile rainbow trout has shown seasonal reductions in GST activity during the fall-winter seasonal transition (Ronisz et al 1999). The transient increases in GST activity observed in the current study at week 3 may be attributed to increased production of reactive oxygen species at higher temperatures (increasing metabolic rate) eliciting antioxidant responses that may interfere with concurrent thermomodulatory adaptations (Kaur et al 2005). Ration-restricted and fasted fish also exhibit peak GST activities at week 3, but to a lesser extent than seen in control fish.…”
Section: Gst Activitymentioning
confidence: 66%
“…These results suggest GST activity is relatively insensitive to transient temperature changes possibly due to 'positive thermal modulation' whereby Km increases with increasing temperatures (Kennedy et al 1991;Kennedy and Walsh 1994). However, long-term variation in GST activity over seasons has been noted in other aquatic organisms and may be linked to increased metabolic rates at high temperatures (Wilhelm Filho et al 2001;Kaur et al 2005). Furthermore, published work in eelpout and juvenile rainbow trout has shown seasonal reductions in GST activity during the fall-winter seasonal transition (Ronisz et al 1999).…”
Section: Gst Activitymentioning
confidence: 91%
“…Recent studies on intertidal bivalves show that critical warming may exacerbate cellular oxidative stress [43]. In many species, the increase in lipid peroxidation and reactive oxygen species concentration in cells following heat stress has already been shown to modify the activity of antioxidant enzymes such as GPx [44]. Non‐selenium glutathione peroxidase is involved in detoxification by reducing fatty acid hydroxyperoxides and H 2 O 2 [45].…”
Section: Discussionmentioning
confidence: 99%
“…Although copper is an essential micronutrient, it can accumulate and overload hepatocytes, causing liver injury (Pourahmad and O'Brien, 2000). Kaur et al (2005) showed that 3-h heat treatment (from 20 to 32°C) of Channa punctata modulated antioxidant enzymes -GSH, GST, GR, and CAT -in the liver, gill, and kidney. The authors suggested that although the patterns of the increases/ decreases varied among tissues, the changes were unambiguous.…”
Section: Superoxide Dismutase (Sod)mentioning
confidence: 99%